Book Review: Transforming Performance Measurement: Rethinking the Way We Measure and - Chaichukul, Yuttanac (The Journal of Behavioral Science, 2011)
The book is a ―roadmap‖ of success for organizations to develop, improve, and restructure their performance measurement to achieve transformational results that truly and consistently differentiate themselves from competition well into the future. The book imparts key principles that will unlock the full potentials of people in the organization, optimize strategic initiatives, synergize all functional operations, and inspire an organization-wide dynamics of continuous improvement mentality that is the hallmark of a true ―learning organization‖.